RETRACTED: Inhibition of HDAC4 Attenuated JNK/c-Jun-Dependent Neuronal Apoptosis and Early Brain Injury Following Subarachnoid Hemorrhage by Transcriptionally Suppressing MKK7 - Wu, Liqiang; Zeng, Shulian; Cao, Yali; Huang, Ziyan; Liu, Sisi; Peng, Huaidong; Zhi, Cheng; Ma, Shanshan; Hu, Kunhua; Yuan, Zhongmin (Frontiers in Cellular Neuroscience, 2019)
The c-Jun N-terminal kinase (JNK)/c-Jun cascade-dependent neuronal apoptosis has been identified as a central element for early brain injury (EBI) following subarachnoid hemorrhage (SAH), but the molecular mechanism underlying this process are still thoroughly undefined to date. In this study, we found that pan-histone deacetylase (HDAC) inhibition by TSA, SAHA, VPA and M344 led to a remarkable decrease in the phosphorylation of JNK and c-Jun, concomitant with a significant abrogation of apoptosis caused by potassium deprivation in cultured cerebellar granule neurons (CGNs). Further investigation showed that these effects resulted from HDAC inhibition-induced transcriptional suppression of MKK7, a well-known upstream kinase of JNK. Using siRNAs to silence the respective HDAC members, HDAC4 was screened to be required for MKK7 transcription and JNK/c-Jun activation. LMK235, a specific HDAC4 inhibitor, dose-dependently suppressed MKK7 transcription and JNK/c-Jun activity. Functionally, HDAC4 inhibition via knockdown or LMK235 significantly rescued CGN apoptosis induced by potassium deprivation. Moreover, administration of LMK235 remarkably ameliorated the EBI process in SAH rats, associated with an obvious reduction in MKK7 transcription, JNK/c-Jun activity, and neuronal apoptosis. Collectively, the findings provide new insights into the molecular mechanism of neuronal apoptosis regarding HDAC4 in the selective regulation of MKK7 transcription and JNK/c-Jun activity. HDAC4 inhibition could be a potential alternative to prevent MKK7/JNK/c-Jun axis-mediated nervous disorders, including SAH-caused EBI.